Faktor Domestik di Balik Kerjasama Ekonomi: Kebijakan Jepang terhadap Indonesia dalam Skema Indonesia-Japan Economic Partnership Agreement (IJ-EPA) 2008 – 2018 - Dian Islamawati; Mohamad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The end of Japanese occupation during World War II made Japan finally provide war compensation assistance to its former colonies, including Indonesia, known as Japan ODA assistance. Over time, this assistance was also used by Japan as a means of maintaining good relations between Japan and Indonesia. After the ODA assistance took place for 50 years (1958-2008), then in 2008 Japan and Indonesia entered into bilateral economic cooperation through the Indonesia-Japan Economic Partnership Agreement (IJ-EPA) scheme. However, the cooperation that has been carried out for 10 years (2008-2018) has resulted an imbalance because the economic benefits were dominated by the Japanese, while the benefits gained by Indonesia were not significant. In addition to the economy, Japanese policy in the IJ-EPA is also used to dominate other fields. This research then aims to analyze the reasons why Japan is willing to conduct bilateral economic cooperation with Indonesia. There are domestic factors behind Japan cooperating with Indonesia through the IJ-EPA scheme. These factors will be analyzed using the concept of national interest and nation branding. This study argues that the IJ-EPA cooperation between Japan and Indonesia in the end only benefited the Japanese. Because besides dominating profits in the economic field, the IJ-EPA collaboration was also used by Japan to maintain its dominance in Southeast Asia.